PENGEMBANGAN KETRAMPILAN PUBLIC SPEAKING DAN SELF LEADERSHIP UNTUK MEMPERKUAT KEMAMPUAN INTERPERSONAL WIRAUSAHA MUDA - Kurniawati, Desi Tri; Noermijati, Noermijati; F, Muhammad (Politeknik Negeri Sriwijaya, 2024)
The role of entrepreneurship in development and the national economy encourages an increase in entrepreneurs every year. The government and educational institutions are trying to encourage the growth of entrepreneurs. The development of entrepreneurial actors is considered very important in realizing the economic independence of society. Apart from that, the growth of business actors, especially those from the younger generation, can reduce challenges in facing the demographic bonus. The existence of young entrepreneurs can increase labor absorption and improve social welfare. The availability of employment opportunities encourages strengthening national development because higher access to employment opportunities will increase consumption levels and community independence. Entrepreneurship has now become an indicator for measuring the success of a country, therefore strengthening the abilities of business actors, especially young entrepreneurs, is very necessary. The service activities that have been carried out are aimed at improving the communication skills of young entrepreneurs. Communication skills are an important aspect to maintain business continuity. Young entrepreneurs need communication skills in carrying out business activities such as business negotiations, pitching, and motivating employees. Apart from communication training, young entrepreneurs will also be given training in managing self-leadership. Through communication and self-leadership training, young entrepreneurs are targeted to be able to make measured decisions and achieve business success effectively. Implementation of service activities is carried out directly using intensive mentoring methods and collaborating directly with the FEB UB Entrepreneurship Laboratory. The impact of collaborative community service activities in 2023 is expected to be able to improve the communication and leadership skills of young entrepreneurs within Universitas Brawijaya